Distributed thermometry for superconducting magnets using non-leaky acoustic waveguides. (17th February 2023) - Marchevsky, M; Prestemon, S
Abstract: Distributed temperature sensing is the preferred approach for detecting and localizing normal zones in the high-field magnets of particle accelerators and fusion energy systems based on high-temperature superconductors. Optical fibers show promise in realizing this approach but suffer from known drawbacks, such as fiber fragility and cross-sensitivity to strain. Guided acoustic wave-based thermometry is a viable alternative to fiber optics; however, its application is currently limited by the leaky nature of wave propagation in acoustic waveguides. We propose the novel concept of a cladded acoustic waveguide in which, due to the elimination of the adhesion between the core and cladding, propagation of longitudinal acoustic excitations is sustained over long distances without leaking wave energy to the environment. These acoustic fibers can be structurally integrated into superconducting magnets and enable the distributed detection of local heating via thermally driven variations in the sound velocity. We present the practical design of acoustic fibers and the results of the experimental detection and localization of heat sources using our technique under ambient and cryogenic conditions. The prospects of using this technique for superconducting magnet quench diagnostics are discussed.